EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAWDAN GROUP INVESTIGATION (GI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI GENDER - Muhammad Jainuri; Awatif; Winda Blizinky (Matedukasia, 2023)
his study aims to determine and describe the ability to solve mathematical problems in terms of gender using a jigsaw cooperative learning model better than group investigation (GI) of class XI students of SMA Negeri 1 Merangin. This study used a quantitative approach, experimental method with a 2 x 2 factorial design with a population of 5 classes of students in class XI IPA. The sampling technique used Simple Random Sampling, the selected sample was class XI IPA 1 as the experimental class 1 by applying the Jigsaw type cooperative learning model and XI IPA 2 as the experimental class 2 by applying the Group Investigation (GI) cooperative learning model and the two classes were grouped based on the gender of male students and female students. Data collection techniques through a description test of mathematical problem solving abilities. From the results of data analysis shows that hypothesis 1 obtained  or, and hypothesis 2 is obtained  it can be concluded: the ability to solve mathematical problems using the jigsaw cooperative learning model is better than group investigation (GI) in terms of all students and the gender of male students, hypothesis 3 is obtained or which means that the ability to solve mathematical problems using the jigsaw cooperative learning model is not better or the same as group investigation (GI) in terms of the gender of female students. Furthermore, hypothesis 4 is obtained or 3,67 < 3,99 with the conclusion that there is no interaction between the Jigsaw cooperative learning model and Group Investigation (GI) in terms of student gender in influencing students' mathematical problem solving abilities